2018
DOI: 10.31887/dcns.2018.20.3/pschulz
|View full text |Cite
|
Sign up to set email alerts
|

Alternative and complementary approaches in psychiatry: beliefs versus evidence

Abstract: While the legitimacy of medical treatments is more and more questioned, one sees a paradoxical increase in nonconventional approaches, notably so in psychiatry. Over time, approaches that were considered valuable by the scientific community were found to be inefficacious, while other approaches, labelled as alternative or complementary, were finally discovered to be useful in a few indications. From this observation, we propose to classify therapies as orthodox (scientifically validated) or heterodox (scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Regarding the reason why older people had lower CAM utilization, one reason may be the risk of virus infection for older adults influence them to go out during the COVID-19 outbreak or visit CAM institution. Another possible reasons might be a lack of trained CAM practitioners to give them accurate advice, such as how to use aromatherapy, physical therapy, art therapies, and so on [ 19 , 35 ]. The other reason might be influenced by healthcare spending regarding the use of CAMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the reason why older people had lower CAM utilization, one reason may be the risk of virus infection for older adults influence them to go out during the COVID-19 outbreak or visit CAM institution. Another possible reasons might be a lack of trained CAM practitioners to give them accurate advice, such as how to use aromatherapy, physical therapy, art therapies, and so on [ 19 , 35 ]. The other reason might be influenced by healthcare spending regarding the use of CAMs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that up to 80% of the general population used at least one CAM in the past year. The reasons why they seek CAMs included enhancing disease-fighting properties through antioxidant supplements, improving disease-specific quality of life, increasing vital energy flow, and improving their physical and mental health [ 18 , 19 , 20 ]. Traditional Chinses medicine (TCM) treatments or herbal products, muscle relaxation techniques (e.g., yoga, massage, tai chi, dance, and exercise), functional food and dietary supplements (e.g., probiotics and vitamin D), mindfulness activities (e.g., Ayurveda and Reiki), and aromatherapy were the most popular CAM interventions used at home to ease the symptoms induced by COVID-19 infection, support the immune system to avoid infection, or promote psychological wellbeing in order to return to normal life during this stressful time [ 10 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This lack of access may be due to a shortage of quali ed therapists, physicians who are reluctant to recommend evidence-based psychotherapies or have insu cient budgets for non-pharmacological therapies. Furthermore, psychotropic drugs are not consistently e cient and cause side effects (Schulz & Hede, 2018). Overall, despite a variety of treatment choices, full recovery is seldom achieved and it is necessary to investigate new therapeutic alternatives to offer different remedies for individuals suffering from anxiety disorders (Hyde et al, 2019;Shvil et al, 2013) and given the high cost and unfavorable results linked to GAD, an up-to-date critical comparison of the different therapies is crucial (Carl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%